Research Network on Regional Economic and Policy History. (3rd July 2017) - Molema, Marijn; van der Zwet, Arno
ABSTRACT: In the spring of 2017, the Research Network on Regional Economic and Policy History organized its inaugural workshop in London. The network aims to stimulate research in relation to regional economic development and planning challenges, by exploring the importance of historical approaches and methodologies whilst uncovering linkages between historical science and regional studies. The added value of an historical perspective is that it assists in revealing path dependencies in a region's economy. Moreover, it can provide learnings in terms of the successes and failures of policy instruments, strategies, and institutions that are responsible for the implementation of regional policy. Furthermore, history can provide much-needed 'thick' descriptions which highlight contingencies. This contribution first explores the perspectives for interdisciplinary exchange between the study of history and the fields of regional and planning studies. Subsequently, it provides an outline of the aims and objectives, key activities, and participants of the network.